Scale insect genus names and their families in the scale insects (Hemiptera: Sternorrhyncha: Coccomorpha), a supplement - Williams, Douglas J.; Denno, Barbara D. (Zootaxa, 2020)
A list of genus names in the scale insects published between 2014 and the end of 2019 is provided; it follows on from an earlier comprehensive list of the names published between 1758 and the end of 2013. Each genus name and its type species are assigned to one of the 53 scale insect families now recognised.